PENGARUH NON PERFORMING FINANCING (NPF), RETURN ON ASSET (ROA), DAN FINANCING TO DEPOSIT RATIO (FDR) TERHADAP CAPITAL ADEQUACY RATIO (CAR) - Erwin Putra Yokoyama; Dewa Putra Khrisna Mahardika (Jurnal Ilmiah MEA (Manajemen, Ekonomi, & Akuntansi), 2019)
Islamic banking is one of the financial institutions being developed in Indonesia. One reason for developing Islamic banking is the long-term effect provided by Islamic banking, which is immune or has no effect if inflation occurs. CAR is a bank's performance ratio to measure the capital adequacy of a bank to support assets that contain or produce risks The purpose of this study was to determine the effect of Non Performing Financing (NPF), Return on Assets (ROA), and Financing to Deposit Ratio (FDR) to the Capital Adequacy Ratio (CAR). The sample selection technique used was purposive sampling and obtained by 12 Sharia Commercial Banks with a research period in 2013-2017. The population in this study is Islamic Commercial Banks. The sample selection technique used was purposive sampling and obtained by 12 Sharia Commercial Banks with a research period in 2013-2017. The method of data analysis in this study is panel data regression analysis. The results showed that simultaneously Non Performing Financing (NPF), Return on Assets (ROA), and Financing to Deposit Ratio (FDR) had a significant effect on Capital Adequacy Ratio (CAR). While partially, Non Performing Financing (NPF) has a positive effect on Capital Adequacy Ratio (CAR). Return on Assets (ROA) has a positive effect on Capital Adequacy Ratio (CAR). Financing to Deposit Ratio (FDR) has a negative effect on Capital Adequacy Ratio (CAR).